2020
DOI: 10.1037/ppm0000248
|View full text |Cite
|
Sign up to set email alerts
|

Entertainment motivations and gaming-specific gratifications as antecedents of digital game enjoyment and appreciation.

Abstract: Media psychological research has identified a broad range of gratifications that can result from playing digital games and fuel players' entertainment experiences. Most of these studies focused on pleasurable, hedonic entertainment experiences (i.e., enjoyment). However, scholarship increasingly acknowledges that digital games can also offer more profound (eudaimonic) entertainment experiences, characterized by the feeling of being moved and the experience of meaningfulness (i.e., appreciation). Knowledge abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 46 publications
2
44
0
Order By: Relevance
“…However, it is also plausible that players do not specifically turn to games in the search for meaning, personal growth or being moved, but are rather primarily motivated by experiencing pleasure. Hence, eudaimonic experiences may be states that players 'happen to find' while being 'on the road to fun' (Possler et al, 2020). Additionally, only two studies in our review dealt with self-transcendent experiences and related emotions such as elevation (P23, P25).…”
Section: Advancing Research On Eudaimonia In Digital Gamesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also plausible that players do not specifically turn to games in the search for meaning, personal growth or being moved, but are rather primarily motivated by experiencing pleasure. Hence, eudaimonic experiences may be states that players 'happen to find' while being 'on the road to fun' (Possler et al, 2020). Additionally, only two studies in our review dealt with self-transcendent experiences and related emotions such as elevation (P23, P25).…”
Section: Advancing Research On Eudaimonia In Digital Gamesmentioning
confidence: 99%
“…In line with the evolution of the medium, scholars from different research fields increasingly view digital games not solely as 'fun machines' that offer their players rich hedonic experiences such as enjoyment, but are beginning to shed light on more complex, fundamental reactions to games . Echoing recent developments in entertainment research (Vorderer & Reinecke, 2015), human-computer interaction (HCI; Bopp, Mekler, & Opwis, 2016), and positive psychology (Ryan & Deci, 2001), these profound dimensions of the digital game experience have often been labelled 'eudaimonic' (e.g., Daneels, Vandebosch, & Walrave, 2020;Oliver et al, 2016;Possler, Kümpel, & Unkel, 2020). However, these and other studies across multiple fields of research on eudaimonic game experiences employ a great range of concepts, which are often used synonymously and/or are not clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Research has also shown that narratives are more powerful and impactful when people are engaged with them (Nabi & Green, 2015). Linking this to eudaimonic experiences, research on awe-inspiring game experiences by Possler, Kümpel, and Unkel (2019), for example, has found that feeling engaged with the game's narrative can account for the occurrence of eudaimonic game experiences. However, little research to date has directly examined the link between narrative engagement and eudaimonic game experiences.…”
Section: Narrative Characteristics and Player-narrative Interactionsmentioning
confidence: 99%
“…Past research has found that mechanical gratifications only relate to hedonic experiences or enjoyment (Kümpel & Unkel, 2017;Oliver et al, 2016). However, other studies support the notion that game mechanics can enhance and augment the game narrative, leading to both the narrative and mechanics being important catalysts of eudaimonic experiences (Iten et al, 2018;Possler et al, 2019).…”
Section: Eudaimonic Experiences Through Digital Game Mechanicsmentioning
confidence: 99%
“…Building on the notions of hedonic and eudaimonic well-being in positive psychology (Ryan & Deci, 2001), we differentiate two types of game experience: hedonic and eudaimonic. While hedonic experience focuses on game enjoyment, eudaimonic describes experience that is beyond basic pleasure, for instance self-acceptance and human virtue (Oliver et al, 2018;Possler et al, 2020). Thus, the main purpose of our research is to underpin how an in-game purchase is motivated by the pursuit of eudaimonic game experience in the context of MMORPGs.…”
mentioning
confidence: 99%